The Politics of the Pharmaceutical Industry and Access to Medicines
1 online resource (xx, 370 pages)
Keywords: "The book studies the pharmaceutical industry of India. It is one of the most successful stories of economic expansion and improvements in public health. Indian firms have made access to quality medicines possible and affordable in many developing countries. Indian pharmaceuticals are also exported on a large scale to the United States and other highly regulated markets. A wave of mergers, acquisitions and tie-ups point to growing integration between Indian firms and global pharma multinationals."--Provided by publisher.